Republished: Interprofessional education in team communication: working together to improve patient safety. Issue 1057 (15th October 2013) - Brock, Douglas; Abu-Rish, Erin; Chiu, Chia-Ru; Hammer, Dana; Wilson, Sharon; Vorvick, Linda; Blondon, Katherine; Schaad, Douglas; Liner, Debra; Zierler, Brenda
Abstract : Background: Communication failures in healthcare teams are associated with medical errors and negative health outcomes. These findings have increased emphasis on training future health professionals to work effectively within teams. The Team Strategies and Tools to Enhance Performance and Patient Safety (TeamSTEPPS) communication training model, widely employed to train healthcare teams, has been less commonly used to train student interprofessional teams. The present study reports the effectiveness of a simulation-based interprofessional TeamSTEPPS training in impacting student attitudes, knowledge and skills around interprofessional communication. Methods: Three hundred and six fourth-year medical, third-year nursing, second-year pharmacy and second-year physician assistant students took part in a 4 h training that included a 1 h TeamSTEPPS didactic session and three 1 h team simulation and feedback sessions. Students worked in groups balanced by a professional programme in a self-selected focal area (adult acute, paediatric, obstetrics). Preassessments and postassessments were used for examining attitudes, beliefs and reported opportunities to observe or participate in team communication behaviours. Results: One hundred and forty-nine students (48.7%) completed the preassessments and postassessments. Significant differences were found for attitudes toward team communication (p<0.001), motivation (p<0.001), utility of training (p<0.001) and self-efficacy (p=0.005). Significant attitudinal shifts for TeamSTEPPS skills included, team structure (p=0.002), situation monitoring (p<0.001), mutual support (p=0.003) and communication (p=0.002). Significant shifts were reported for knowledge of TeamSTEPPS (p<0.001), advocating for patients (p<0.001) and communicating in interprofessional teams (p<0.001). Conclusions: Effective team communication is important in patient safety. We demonstrate positive attitudinal and knowledge effects in a large-scale interprofessional TeamSTEPPS-based training involving four student professions.